Soyons réalistes, demandons l’impossible ! Courbet 68 - Desbuissons, Frédérique (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2019)
Shot in 1967 and released in March 1968, by the young, engaged filmmaker Charles Belmont, Mood Indigo is a political interpretation of Boris Vian’s novel of 1947. The poetic world of Vian, mixing surrealism with jazz and symbolist literature, intersects in the film with references to 19th-century realist painting by Courbet and Millet. These appear as pictures on the walls, transformed into tableaux vivants, or as a personification of Courbet wandering in the landscape. Such paradoxical mobilization of realist painting, which professed to exclude the imagination, needs be considered as constituting a case of the reception of realism in the context of 1968. Over and beyond witnessing how “bourgeois” investments in the cultural heritage could be targeted on the part of militants of the extreme left, Mood Indigo contributes to the subversion of the traditional opposition between the real and the imaginary underlying the mythic graffiti “Be realistic, demand the impossible” that flourished on the walls of Paris that Spring.